2017 Update on the Querleu-Morrow Classification of Radical Hysterectomy - Querleu, Denis; Cibula, David; Abu-Rustum, Nadeem R (Annals of surgical oncology, 2017)
BACKGROUND: One of the most important principles in modern cervical cancer surgery is the concept of tailoring surgical radicality. In practice, this means abandoning the "one-fits-all" concept in favor of tailored operations. The term "radical hysterectomy" is used to describe many different procedures, each with a different degree of radicality. Anatomic structures are subjected to artificial dissection artifacts, as well as different interpretations and nomenclatures. This study aimed to refine and standardize the principles and descriptions of the different classes of radical hysterectomy as defined in the Querleu-Morrow classification and to propose its universal applicability. METHODS: All three authors independently examined the current literature and undertook a critical assessment of the original classification. Images and pathologic slides demonstrating different types of radical hysterectomy were examined to document a consensual vision of the anatomy. The Cibula 3-D concept also was included in this update. RESULTS: The Querleu-Morrow classification is based on the lateral extent of resection. Four types of radical hysterectomy are described, including a limited number of subtypes when necessary. Two major objectives remain constant: excision of central tumor with clear margins and removal of any potential sites of nodal metastasis. CONCLUSION: Studies evaluating radicality in the surgical management of cervical cancer should be based on precise, universally accepted descriptions. The authors' updated classification presents standardized, universally applicable descriptions of different types of hysterectomies performed worldwide, categorized according to degree of radicality, independently of theoretical considerations.
Keywords: lymfadenektomie; Uterine Cervical Neoplasms; ženské pohlaví; prognóza; hysterektomie; Lymph Node Excision; Humans; Hysterectomy; Female; nádory děložního čípku; Prognosis; lidé